Az episztémé, mint a kapcsolatiság eleme - TÓDOR, Csaba (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
Episteme as an Element of Relationality. The concepts of phenomenological archaeology and episteme explore the structural conditions shaping an era’s knowledge and cultural paradigms. Foucault’s notion of episteme emphasizes the historical rules and hidden assumptions underlying knowledge, diverging from the universalism of transcendental philosophy. Archaeological hermeneutics reconstructs the emergence and impact of epistemes, reflecting dynamic social, cultural, and political transformations. Historical epistemic shifts span four major phases: from Semitic to Greco-Roman paradigms, the influence of Germanic tribes on Christian thought, the Aristotelian revival between the 12th and 16th centuries, and the current postmodern, globalized context. Theological renewal, driven by relational epistemology, engages with multiculturalism, globalization, and interreligious dialogue, necessitating the critical reconstruction of scholastic traditions. The phenomenological archaeology of Husserl, Merleau-Ponty, and Foucault moves beyond transcendentalist truth claims to examine the historical contingencies and unconscious frameworks shaping knowledge and discourse.